A microfluidic chip with gravity-induced unidirectional flow for perfusion cell culture - Lee, Dong Wook; Choi, Nakwon; Sung, Jong Hwan (WILEY, 2019)
Perfusion flow is one of the essential elements and advantages of organ-on-a-chip technology. For example, microfluidics have enabled implementation of perfusion flow and recapitulation of fluidic environment for vascular endothelial cells. The most prevalent method of implementing flow in a chip is to use a pump, which requires elaborate manipulation and complex connections, and accompanies a large amount of dead volume. Previously we devised a gravity-induced flow system which does not require tubing connections, but this method results in bidirectional flow to enable recirculation, which is somewhat different from physiological blood flow. Here, we have developed a novel microfluidic chip that enables gravity-induced, unidirectional flow by using a bypass channel with geometry different from the main channel. Human umbilical vein endothelial cells were cultured inside the chip and the effect of flow direction was examined. (c) 2018 American Institute of Chemical Engineers Biotechnol. Prog., 35: e2701, 2019
Keywords: ON-A-CHIP; ORGAN SYSTEMS; SHEAR-STRESS; PLATFORM; DEVICE; LIVER; COCULTURE; MODELS; HEART